The Relevance of Work Ethics and Productivity in the Theory of Al-Kasb Asy-Syaibani - Lamondo, Lamondo; Sabon, Nurmala N (Li Falah: Journal of Islamic Economics and Business, 2022)
Al-Syaibani is a significant scholar and economic thinker who is an Abu Hanifah student focusing on microeconomics. Al-Syaibani's economic thoughts can be seen in Kitab al-Kasb, al-Ikhtisab fi al-Rizq al-Mustahab, and Kitab al-Asl, which discuss income, guidelines for production and consumption behaviour, various forms of business such as trade, agriculture, industry and agreements. Work. Al-Syaibani's economic thinking in a modern context is still very relevant, especially in the concepts of al-kasb and al-Ikhtisab, which must refer to usability and usefulness. This research uses a literature study to examine the theory of al-kasb asyibani and its relevance to Indonesia's economic growth. The relevance found between al Kasba asy Syaibani's theory regarding the obligation to work, which is a production activity, is very closely related to the work ethic and productivity theory that in productivity, one of the most important facts is labour, in line with this to create high productivity there is an additional factor of human resources work the quality of its workforce accompanies that.